Traces of the Art of Governing People (KULT_online, 2018)
In his new book Gute Hirten führen sanft, Ulrich Bröckling assembles theoretically as well as empirically oriented essays. The collected works firstly point out the premises of a research program inspired by the work of Michel Foucault; secondly, they exemplify this agenda through several individual studies treating empirical subjects; finally, they offer insights into the relationship of critique, counter-action, and sociology. The recurring theme of these essays is the rise of a subtle, consensus-oriented form of government and the effects of domination it bears.